Ngusaba Gede Ceremony in Demulih Village, Susut District, Bangli Regency - Ni Nengah Dea Ayu Ferina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study looks at the meaning of the Ngusaba Gede ceremony in Demulih Village, Susut District, Bangli. Previous studies related to the issue of the Ngusaba Ceremony have focused on Hindu religious education, while not many have highlighted the Ngusaba ceremony in terms of its meaning. By taking the case of the Ngusaba Dalem Ceremony in Demulih Village, it uses the concept of Clifford Geertz related to the problem of meaning which looks at the interpretive culture in which there is a concept of model of which looks at religious morality, namely where religion becomes knowledge for the people of Demulih Village in carrying out the ceremony Ngusaba Gede and the model for are seen in the reality that occurs in this ngusaba ceremony which is contained in the holy book that is believed by the people of Demulih Village, thus giving rise to the meaning of this Ngusaba Gede ceremony, namely that there is a religious symbol called Nawa Sanga (Nine gods) and symbols of structures related to it with the ceremonial leader Ngusaba Gede. The method used in this study uses qualitative methods, namely by means of observation, in-depth interviews, and field notes.